2022
DOI: 10.3390/ph15050612
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brain Modulators in Neurodevelopment: Focus on Autism Spectrum Disorder and Associated Comorbidities

Abstract: Autism spectrum disorder (ASD) and associated neurodevelopmental disorders share similar pathogenesis and clinical features. Pathophysiological changes in these diseases are rooted in early neuronal stem cells in the uterus. Several genetic and environmental factors potentially perturb neurogenesis and synaptogenesis processes causing incomplete or altered maturation of the brain that precedes the symptomology later in life. In this review, the impact of several endogenous neuromodulators and pharmacological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 202 publications
(299 reference statements)
0
4
0
2
Order By: Relevance
“…Considering HAND and other neurodegenerative conditions are often associated with aging, these more subtle mechanisms may accumulate over time to become major contributors to disease onset and progression. Sub-neurotoxic models can also be useful in neuropsychiatric disorders featuring altered neuronal activity without cell death, and in studies of neurodevelopmental disorders, where affected neurons are not yet synaptically mature ( Habela et al, 2016 ; Sabitha et al, 2021 ; Saad et al, 2022 ). One particular sub-neurotoxic phenotype that is relevant in neurodevelopmental disorders is alterations in spine density and morphology, which would not have been captured via our studies of MAP2 morphology and may underlie some the observed changes in neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering HAND and other neurodegenerative conditions are often associated with aging, these more subtle mechanisms may accumulate over time to become major contributors to disease onset and progression. Sub-neurotoxic models can also be useful in neuropsychiatric disorders featuring altered neuronal activity without cell death, and in studies of neurodevelopmental disorders, where affected neurons are not yet synaptically mature ( Habela et al, 2016 ; Sabitha et al, 2021 ; Saad et al, 2022 ). One particular sub-neurotoxic phenotype that is relevant in neurodevelopmental disorders is alterations in spine density and morphology, which would not have been captured via our studies of MAP2 morphology and may underlie some the observed changes in neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Przyczyną takiego upośledzenia mogą być mutacje genetyczne bądź urazy środowiskowe, w tym środki farmakologiczne stosowane klinicznie w czasie ciąży. 5 ADHD jest zaliczane do zaburzeń neurorozwojowych, którego etiologia nie została jeszcze dokładnie poznana. 6 Takie zaburzenia w rozwoju ośrodkowego układu nerwowego obejmują upośledzenie kilku układów neuromodulatorów.…”
Section: Wstępunclassified
“…6 Takie zaburzenia w rozwoju ośrodkowego układu nerwowego obejmują upośledzenie kilku układów neuromodulatorów. 5 Dopamina (DA) i noradrenalina (NA), które są syntetyzowane z L-DOPA, odgrywają istotną rolę w skupianiu uwagi i koncentracji, odpowiadają za motywację, czujność oraz zachowania związane z nagrodą. Leki które używa się do leczenia ADHD wpływają zatem zarówno na układ DA, jak i NA 6 .…”
Section: Wstępunclassified
“…However, the autism spectrum disorder is a complex neurodevelopmental condition, and environmental and genetic factors are proposed to contribute to the disorder pathogenesis (Eve et al 2022). Dopamine is involved in neurogenesis, neuronal migration, and synaptogenesis (Saad et al 2022), and perturbations in dopaminergic innervation and transmission have therefore been proposed to participate in the etiology of the autism spectrum disorder. Although in this study animals were exposed to PM in their adult life, changes in dopaminergic transmission in adulthood could also mimic, at least to some extent, behavioral changes originated by altered development of the brain dopaminergic systems.…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%